Surface roughness and directional fatigue behavior of as-built EBM and DMLS Ti6Al4V. (November 2018) - Nicoletto, G.; Konečná, R.; Frkáň, M.; Riva, E.
Highlights: Fatigue strength and surface roughness of as-built DMSL Ti64 and EBM Ti64 are determined and compared. As-built DMSL Ti64 shows higher fatigue strength than as-built EBM Ti64. A new test method using mini specimens conveniently provides knowledge on PBF metals fatigue. The present fatigue data are coherent with data obtained with standard specimens and test methods. Abstract: The powder bed fusion PBF is used in the fabrication layer-by-layer of metallic parts directly from a CAD file. Localized powder melting is obtained by a concentrated energy source. Fatigue tests of PBF Ti6Al4V were performed on smooth specimens produced with different orientations with respect to build direction using either a laser beam system (DMLS) or an electron beam system (EBM). As-built specimen were subjected the fatigue loading to understand and quantify the influence of the surface roughness and morphology. The original results are discussed on the basis of previous studies on the same material and processes taken from the literature.